THE ROLE OF ONLINE TOURIST AGENCIES IN THE DEVELOPMENT OF HALAL TOURISM - Barotov Umidjon Mahmud o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the growing commitment to addressing the unique requirements of Muslim travelers within the global hospitality and tourism sector. It delves into the three primary reasons behind this trend, namely the lifestyle-oriented approach to Islam, the increasing income and economic prosperity of Muslim-majority countries, and the burgeoning market for halal tourism. The article also highlights the potential market opportunities presented by catering to the faith-based needs of Muslim tourists and emphasizes the significance of adapting to these evolving demands within the hospitality industry. Online tourist agencies play a crucial role in shaping the needs of Muslim travelers in the growing Halal tourism industry. The increasing Muslim population and their rising disposable income have resulted in more Muslims engaging in travel for various purposes, including leisure, business, health, and religious activities. As a result, Muslim travelers have emerged as one of the fastest-growing segments in the tourism industry.